Determination of 13C/12C ratios of endogenous urinary 5‐amino‐imidazole‐4‐carboxamide 1β‐D‐ribofuranoside (AICAR). (10th April 2014) - Piper, Thomas; Thomas, Andreas; Baume, Norbert; Sobolevsky, Timothy; Saugy, Martial; Rodchenkov, Grigory; Schänzer, Wilhelm; Thevis, Mario
<x xml:space="preserve">Abstract</x> RATIONALE AICAR (5‐aminoimidazole‐4‐carboxamide 1β‐D‐ribofuranoside) is prohibited in sport according to rules established by the World Anti‐Doping Agency. Doping control laboratories identify samples where AICAR abuse is suspected by measuring its urinary concentration and comparing the observed level with naturally occurring concentrations. As the inter‐individual variance of urinary AICAR concentrations is large, this approach requires a complementary method to unambiguously prove the exogenous origin of AICAR. Therefore, a method for the determination of carbon isotope ratios (CIRs) of urinary AICAR has been developed and validated. METHODS Concentrated urine samples were fractionated by means of liquid chromatography for analyte cleanup. Derivatization of AICAR yielding the trimethylsilylated analog was necessary to enable CIR determinations by gas chromatography/combustion/isotope ratio mass spectrometry. The method was tested for its repeatability and stability over time and a linear mixing model was applied to test for possible isotopic discrimination. A reference population of n = 63 males and females was investigated to calculate appropriate reference limits to differentiate endogenous from exogenous urinary AICAR. These limits were tested by an AICAR elimination study. RESULTS The developed method fulfills all the requirements for adequate sports drug testing and was found to be fit for purpose. The investigated reference population showed a larger variability in the CIR of AICAR than of the endogenous steroids. Nevertheless, the calculated thresholds for differences between AICAR and endogenous steroids can be applied straightforwardly to evaluate suspicious doping control samples with the same statistical confidence as established e.g. for testosterone misuse. These thresholds enabled the detection of a single oral AICAR administration for more than 40 h. CONCLUSIONS Determination of thee CIRs is the method of choice to distinguish between an endogenous and an exogenous source of urinary AICAR. The developed method will enable investigations into doping control samples with elevated urinary concentrations of AICAR and clearly differentiate between naturally produced/elevated and illicitly administered AICAR. Copyright © 2014 John Wiley & Sons, Ltd.